A comparison between fracture toughness at different locations of SMAW and GTAW welded joints of primary coolant piping. (15th October 2018) - Yu, Weiwei; Fan, Minyu; Shi, Jinhua; Xue, Fei; Chen, Xu; Liu, Hui
Highlights: Two kinds of welded joints of primary coolant pipes were studied for fracture toughness measure. Fracture toughness has been investigated at different locations of the SMAW and GTAW welded joints. Fusion zones (FZs) have the worst fracture toughness. GTAW welded joints have a better comprehensive performance than the SMAW welded joints. Abstract: Two primary coolant pipes were narrow-gap multipass circumferentially butt welded by gas tungsten arc welding (GTAW) and shielded metal arc welding (SMAW) methods separately and then subjected to micro-hardness tests to distinguish the base metal (BM), heat affected zones (HAZs), fusion zones (FZs) and weld metal (WM). Subsequently, uniaxial tensile tests were performed with a 3D DIC system to investigate the strain evolution of each area in GTAW and SMAW welded joints and to compare respective tensile properties. The fracture toughness has been investigated at the above four different locations of the SMAW and GTAW welded joints. Then the 0.2 mm offset line method and the stretch zone width method have been both employed to determine the critical initial fracture toughness J i . The results indicate that the fusion zones (FZs) have the worst fracture toughness compared with other locations over both two types of weld joints. In addition, the GTAW welded joints have a better comprehensive performance than the SMAW welded joints.